The inhibitory effect of Camellia sinensis extracts against the neuromuscular blockade of Crotalus durissus terrificus venom - de Jesus Reis Rosa, Luana (Library Publishing Media, 2010)
In geographically isolated populations where intensive medical care or serum therapy is not easily accessible snake envenomation is a major cause for concern. The aim of the present study was to test Camellia sinensis extracts, theaflavin and epigallocatechin (two of the main C. sinensis components) against the irreversible neuromuscular blockade induced by Crotalus durissus terrificus venom in mouse phrenic-nerve diaphragm preparations. A quantitative histological study was also performed. The venom (20µg/ml) completely decreased twitch tension after 70min and 5µg/ml venom abolished 50% of twitch amplitude after 60min. C. sinensis extract induced intense facilitatory effect in the preparation activity at 0.2mg/ml and slightly facilitatory effect at 0.05mg/ml. Both 0.05mg/ml C. sinensis extract and 0.05mg/ml commercial theaflavin maintained partial muscular activity in presence of 5µg/ml venom. The histological data confirms that Cs is able to protect the muscle from the myotoxic activity of the venom. Commercial epigallocatechin gallate did not show pre-synaptic nor post-synaptic activities. C. sinensis extract was able to protect the mouse phrenic-nerve diaphragm against the irreversible neuromuscular blockade induced by C. durissus terrificus venom.